2005
DOI: 10.1196/annals.1345.065
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model to Assess and Improve Adherence to Iron Chelation Therapy with Deferoxamine in Patients with Thalassemia

Abstract: Adherence to deferoxamine (DFO) is vital for the long-term survival of patients with thalassemia; however, currently no measure exists to quantify adherence directly. In this study, 90 patients with thalassemia major underwent liver iron concentration (LIC) assessment by SQUID biosusceptometer, were asked to rate their adherence to DFO using a Numerical Likert Scale (NLS), and were educated about complications of iron overload. Of 38% (n = 28) of patients who rated themselves as very compliant, 19 had elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…The body iron burden of the cohort as measured by the geometrical mean LIC decreased significantly during the period of access to non‐invasive LIC measurement. The significant decrease in the body iron burden together with the documented clinical decisions regarding chelation therapy based on the LIC results are consistent with previous observations that introduction of non‐invasive monitoring of LIC can contribute to a decreased body iron burden through improved clinical decision making and improved feedback to patients and hence improved adherence to chelation therapy 14 . Other factors could also have an effect on the body iron burden of the cohort, such as the introduction of the newly available orally administered chelators, deferiprone and deferasirox.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The body iron burden of the cohort as measured by the geometrical mean LIC decreased significantly during the period of access to non‐invasive LIC measurement. The significant decrease in the body iron burden together with the documented clinical decisions regarding chelation therapy based on the LIC results are consistent with previous observations that introduction of non‐invasive monitoring of LIC can contribute to a decreased body iron burden through improved clinical decision making and improved feedback to patients and hence improved adherence to chelation therapy 14 . Other factors could also have an effect on the body iron burden of the cohort, such as the introduction of the newly available orally administered chelators, deferiprone and deferasirox.…”
Section: Discussionsupporting
confidence: 89%
“…Pakbaz and co‐workers 14 concluded that frequent non‐invasive measurements of LIC using biomagnetic susceptometry together with patient education can improve patient adherence to chelation regimens and result in reduced body iron burdens. Thus, we hypothesise that non‐invasive monitoring of LIC with the R2‐MRI technique 11,12 would aid in reducing the body iron burden in transfused patients through improved quantitative feedback of response of LIC to chelator to both clinician and patient.…”
Section: Introductionmentioning
confidence: 99%
“…Chelation guidelines for sickle-cell syndromes are similar to those for other iron overload situations as thalassemia major and multi-transfused patients [14,15]. Until recently, desferrioxamine and deferiprone were the only active iron-chelating agent approved for clinical use, mainly in the thalassemia setting [16,17]. Recent advances have led to the development of new oral iron chelators, such as deferasirox, which has changed the clinical practice in several transfusiondependent anemias with iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…We have clarified now in the "study design" section that "The starting deferasirox dose was 10 or 20 mg/kg/day depending on previous transfusion requirements: if the patient had received 20-30 red blood cell (RBC) units the dose of 10 mg/kg/day was used; if the patients had received more than 30 RBC units the dose of 20 mg/kg/day was used." [page 4, lines [15][16][17].…”
mentioning
confidence: 99%
“…Likewise, serial LIC measurements that show decreasing LIC can also demonstrate the benefits of chelation to asymptomatic patients and reinforce adherence. Routine education about disease states and chelation therapy has been shown to correlate with improvements in compliance and decreases in LIC . Therefore, patient education and engagement needs to be incorporated into every visit.…”
Section: Clinical Application Of Mri Assessmentsmentioning
confidence: 99%